Ketone Bodies Attenuate Wasting in Models of Atrophy. Issue 4 (2nd April 2020) - Koutnik, Andrew P.; Poff, Angela M.; Ward, Nathan P.; DeBlasi, Janine M.; Soliven, Maricel A.; Romero, Matthew A.; Roberson, Paul A.; Fox, Carl D.; Roberts, Michael D.; D'Agostino, Dominic P.
Abstract: Background: Cancer Anorexia Cachexia Syndrome (CACS) is a distinct atrophy disease negatively influencing multiple aspects of clinical care and patient quality of life. Although it directly causes 20% of all cancer‐related deaths, there are currently no model systems that encompass the entire multifaceted syndrome, nor are there any effective therapeutic treatments. Methods: A novel model of systemic metastasis was evaluated for the comprehensive CACS (metastasis, skeletal muscle and adipose tissue wasting, inflammation, anorexia, anemia, elevated protein breakdown, hypoalbuminemia, and metabolic derangement) in both males and females. Ex vivo skeletal muscle analysis was utilized to determine ubiquitin proteasome degradation pathway activation. A novel ketone diester ( R/S 1, 3‐Butanediol Acetoacetate Diester) was assessed in multifaceted catabolic environments to determine anti‐atrophy efficacy. Results: Here, we show that the VM‐M3 mouse model of systemic metastasis demonstrates a novel, immunocompetent, logistically feasible, repeatable phenotype with progressive tumor growth, spontaneous metastatic spread, and the full multifaceted CACS with sex dimorphisms across tissue wasting. We also demonstrate that the ubiquitin proteasome degradation pathway was significantly upregulated in association with reduced insulin‐like growth factor‐1/insulin and increased FOXO3a activation, but not tumor necrosis factor‐α‐induced nuclear factor‐kappa B activation, driving skeletal muscle atrophy. Additionally, we show that R/S 1, 3‐Butanediol Acetoacetate Diester administration shifted systemic metabolism, attenuated tumor burden indices, reduced atrophy/catabolism and mitigated comorbid symptoms in both CACS and cancer‐independent atrophy environments. Conclusions: Our findings suggest the ketone diester attenuates multifactorial CACS skeletal muscle atrophy and inflammation‐induced catabolism, demonstrating anti‐catabolic effects of ketone bodies in multifactorial atrophy.